2020
DOI: 10.1111/pan.13788
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative identification of children at high risk of obstructive sleep apnea

Abstract: Obstructive sleep apnea is a common childhood disorder which can lead to serious health problems if left untreated. Enlarged adenoid and tonsils are the commonest causes, and adenotonsillectomy is the recommended first line of treatment. Obstructive sleep apnea poses as an anesthetic challenge, and it is a well‐known risk factor for perioperative adverse events. The presence and severity of an obstructive sleep apnea diagnosis will influence anesthesia, pain management, and level of monitoring in recovery peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 109 publications
0
22
0
Order By: Relevance
“…Most commonly used in the perioperative setting include The Snoring, Trouble Breathing, and Un-Refreshed (STBUR) questionnaire and the pediatric sleep questionnaire (PSQ). 13,14 The STBUR is a five-question screening tool to assess for pediatric sleep-disordered breathing and correlates with subsequent perioperative respiratory adverse events risk (snoring, loud snoring, trouble breathing, stopping breathing, unrefreshed in the morning). Although not diagnostic, a score greater than 3 has been shown to have a threefold increase in the likelihood of perioperative respiratory adverse events.…”
Section: Ris K Predic Tion Model S/scoring Tool S and B I Omark Er Te...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly used in the perioperative setting include The Snoring, Trouble Breathing, and Un-Refreshed (STBUR) questionnaire and the pediatric sleep questionnaire (PSQ). 13,14 The STBUR is a five-question screening tool to assess for pediatric sleep-disordered breathing and correlates with subsequent perioperative respiratory adverse events risk (snoring, loud snoring, trouble breathing, stopping breathing, unrefreshed in the morning). Although not diagnostic, a score greater than 3 has been shown to have a threefold increase in the likelihood of perioperative respiratory adverse events.…”
Section: Ris K Predic Tion Model S/scoring Tool S and B I Omark Er Te...mentioning
confidence: 99%
“…27 Classification scoring varies, however, an apnea hypopnea index of 10 or more per hour and/or oxygen saturation nadir of <80% typically represent severe OSA. 14 It is generally believed that those with greater abnormalities on polysomnography are at increased risk of perioperative respiratory complications. 32 Polysomnography is particularly useful in determining the postoperative disposition plan, particularly for those with comorbidities.…”
Section: Upper Respiratory Tract Infections (Urti)mentioning
confidence: 99%
“…Opioid administration can also impair the pharyngeal dilator muscles placing these patients at further risk of upper airway obstruction through airway hypotonia especially in REM sleep. 87,88 Opioid limiting techniques (typically 50% of usual) with a preference of short over long-acting agents have been suggested, in combination with opioid-sparing strategies such as local anesthetic, ketamine, and dexmedetomidine. 23,86 Interestingly, controlled studies demonstrating increased sensitivity to opioid-induced ventilatory depression in children with OSA are limited.…”
Section: Sleep-disordered Breathingmentioning
confidence: 99%
“…There is no standard recognized scoring system that can be universally used across all pediatric age ranges, and a full review can be found elsewhere. 37,38 Briefly, in adolescents with obesity, a 3% oxygen desaturation index <6/h makes important obstructive sleep apnea unlikely. 39 We would suggest use of an index >10/h as a reasonable cutoff for important obstructive or central sleep apnea in this group.…”
Section: Assessment Of Daytime Gas Exchangementioning
confidence: 99%